Gender Matters in Economic Empowerment Interventions : A Research Review - Buvinic, Mayra; O'Donnel, Megan (Published by Oxford University Press on behalf of the World Bank, 2021)
Evidence shows that women face additional constraints because of their gender that affect their economic performance. A review of recent evaluation research demonstrates the types of gender-related constraints women face and the role that economic empowerment interventions can play in overcoming them, especially if they incorporate aspects of smart design, increasing their development impact. The evidence suggests that financial services and training programs are not gender-neutral and that specific design features can yield more positive economic outcomes for women by helping them overcome gender-related constraints. These features include savings and “Graduation” programs that increase women's economic independence, self-reliance and self-control, and the practice of repeated micro-borrowing that increases financial risk-taking and choice. “Smart” design also includes high-quality business management and jobs skills training, and stipends and other incentives in these training programs that address women's and young women's additional time burdens and childcare demands. Peer support may also help to increase financial risk-taking and confidence in business decisions. However, when social norms are too restrictive, and women are prevented from doing any paid work, no design will be smart enough. Subjective economic empowerment appears to be an important intermediate outcome for women that should be promoted and more reliably and accurately measured. Lastly, whenever possible, results should be sex-disaggregated and reported for individuals as well as households.